Impacto del Covid 19 en los indicadores financieros de las instituciones bancarias del Ecuador - Caiza Toaquiza, Tania Maribel (2022)
The banking sector into Ecuador redeems a fundamental role in the economy functioning and development that due to cause Covid-19 has been subject to new implemented parameters, in order to get banking sector better control. This way, the project purpose is to describe the Covid-19 impact onto the banking institutions financial indicators from Ecuador in 6 months, time period, before confinement and 6 months after confinement, which will allow to verify the Ecuadorian banking sector performance, before, the health situation what is living the country. It is applied as a methodology the CAMEL method under financial ratios, what allows banking entities under study state broader vision into aspects such as: Capital, Assets, Administrative Management, Profitability and Liquidity, with a got database of secondary source such as the Banks Superintendence. Besides, it is worked with the sample mean differences method, which allows to observe if the banking sector has had a significant difference, before and after confinement. Into said analysis, it was evidenced, which into 29 of 30 banks analyzed, they were found significant differences and the indicators, and the indicators than the greatest difference are related with the Capital, managerial management and Profitability edges.